A design of influence of gas network parameters on exactness of verification fluidizers domestic gas meters - Середюк, О. Є.; Винничук, А. Г. (METHODS AND DEVICES OF QUALITY CONTROL, 2009)
Mathematical models of gas network physical parametres influence on functioning of mobile verifying installation for common gas meters were analyzed. Experimental researches of the gas network pressure loss established laws with used of the developed experimental installation were carried out. A comparative analysis of theoretical and experimental research results was carried out